EFFECT OF DIFFERENT LEVELS OF SALT AND DROUGHT STRESSES ON GENE EXPRESSION OF TWO TOLERANCE-DIFFERENT TOMATO CULTIVARS IN VITRO - L. K. J. Al-Amery,; Ali H Annon, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A lab experiment was conducted at the Plant Tissue Culture Lab / College of Agricultural Engineering Sciences / University of Baghdad. This experiment was aimed to investigate gene expression index in tomato (Solanum lycopersicum L.) after preparation of salt and simulated drought stresses. Two tomato cultivars were selected which claimed to exhibit different levels of tolerance toward abiotic stresses designated as salt-tolerant Yassamine (Y) and salt-sensitive GS12 (G) to assess the test. Seven day-old seedlings from both cultivars were grown in MS media supplemented with four concentrations of NaCl at 0, 50, 100 and 150 mM and four concentrations of PEG at 0, 10, 20, and 30% for 48 hours. The results were showed that Y cultivar exhibited more proline secretion and chlorophyll content when compared with G. In addition, Y cultivar showed less ion leakage and less affected by elevated abiotic stresses in term of seedling weight variation when compared to G counterparts. The SDS-PAGE gel analysis showed that Y cultivar showed more band intensity when compared with G suggested more corresponding gene expression of tolerant protein against abiotic stresses.